Research on Combustion and Emission Characteristics and Performance Optimization Technology of Hydrogen Internal Combustion Engines - Huang, Jianxiang (Exploring Science Academic Conference Series, 2026)
Against the backdrop of the “Dual Carbon” goals and energy transition, hydrogen internal combustion engines have become an important development direction for hydrogen power by virtue of mature industrial chains and low-cost advantages. Nevertheless, backfire, pre-ignition, high NOₓ emissions and insufficient thermal efficiency remain bottlenecks restricting their large-scale promotion. Experiments show that NOₓ emissions are significantly regulated by the excess air coefficient and reach the peak in the mo derate lean-burn range; under cold start conditions, NOₓ emissions hit the maximum at λ=1.41, with an emission reduction rate of 84.4% when λ drops to 0.72. The adoption of direct in -cylinder injection can fundamentally avoid intake mixture premixing and suppress backfire and pre -ignition. Matching lean combustion, optimized ignition and hydrogen injection strategies as well as eliminating throttle pumping loss can greatly improve in-cylinder combustion quality and thermal efficiency. Based on domestic and overseas research, this paper reviews relevant technical routes, clarifies key optimization methods and technical deficiencies, and offers theoretical references for the engineering calibration and clean, efficient development of hydrogen internal combustion engines.